Medial and lateral osteochondral lesions of the talus treated with double AT-AMIC using a biological scaffold - Soares Baumfeld, Daniel; Soares Baumfeld, Tiago; da Rocha Macedo, Rafael; Costa Machado, Paula; Kuffner, Matheus (Journal of the Foot & Ankle, 2026)
Introduction: Osteochondral lesions of the talus (OLT) are challenging due to poor cartilage healing and the talus’s role in ankle biomechanics. Biological augmentation may improve outcomes. Simultaneous bilateral treatment is rarely reported. This report describes the feasibility and early outcomes of one-stage bilateral arthroscopic OLT treatment. Methods: A 47-year-old man with bilateral OLT and no comorbidities underwent simultaneous bilateral ankle arthroscopy with debridement, microfracture, and implantation of a type I/III collagen scaffold fixed with fibrin glue. Both ankles were immobilized for six weeks, followed by rehabilitation. Results: At three months, the patient showed marked pain reduction, improved range of motion, and functional recovery, with no perioperative or postoperative complications. Conclusions: Simultaneous bilateral arthroscopic treatment of OLT with microfracture and collagen scaffold appears feasible and safe in selected patients, with potential clinical and logistical advantages.